AC-DC UPF charging circuit for two-wheeler electric vehicle application - Swathi Karike; Sudha Rani Donepudi; Kuthuri Narasimha Raju (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
Extinction and the emission of greenhouse gases from fossil fuels led the field of energy studied took a revolutionary turn towards non-conventional natural sources achieving zero-pollution power. Electric vehicles (EVs) are trending in this new era to reduce the global warming. Due to limitations in storage systems, electric vehicles are not much popular but to reduce the pollution from vehicles, EVs are in must condition and recommended for (public/personal) transportation. EV (battery) is charged through a DC source (converting the available AC supply to DC). The conversion process diminishes the input source power factor and is a worrying factor. This paper addresses the power factor issue while charging the battery of EVs. The paper focuses on maintaining the unity power factor on the source side while charging the battery of the EV from AC-DC conversion. The model is developed and the results are discussed (for three different battery levels) using MATLAB/Simulink software.